A disease suppression strategy in action: The impact of non-pharmaceutical interventions in the COVID-19 pandemic in Denmark - Simonsen, Lone; Pedersen, Rasmus Kristoffer; Andreasen, Viggo; Krause, Tyra Grove; Petersen, Eskild (International journal of infectious diseases, 2025)
•Using a NPI suppression strategy, only 7% were infected in the first year of the pandemic in Denmark.•This effective control was achieved without hard lockdown measures.•By summer 2021, 96% of the adults over 50 years of age were fully vaccinated, illustrating a high degree of public trust.•As a result, COVID-19 mortality was 5-10 fold lower than a worst case scenario without NPIs and vaccine protection. When a new pandemic virus emerges in a naive population, the only control options are non-pharmaceutical interventions (NPIs) until vaccines or effective treatments become available. Here, we report on the Danish suppression strategy and use of a combination of NPIs with a notable absence of extremely strict measures (such as stay-at-home orders). Only 7% of Danes were infected (serological evidence) in the first year of the pandemic, compared with 50% in Lombardy in the first wave alone. This low attack rate was accomplished by initial rapid intervention with a free-of-charge mass testing program beginning in October 2020, a strong digital data infrastructure, timely contact tracing and voluntary home isolation, real-time reporting of surveillance data, and a high degree of public trust. The individual contribution of each NPI to the pandemic control is difficult to assess; yet, evidence points to the mass testing program as being particularly effective in removing infected individuals from the pool. In January 2021, vaccines became available, and 96% of Danes over 50 years of age were vaccinated twice with an mRNA vaccine by summer. On February 1, 2022, while facing the Omicron variant and with the older adult newly boosted, Denmark became the first country to drop all NPIs. A few months later, 70% of the population had been infected with the Omicron variant, showing the SARS-CoV-2 transmission potential when unmitigated. Denmark was only close to intensive care unit capacity during the second wave in winter 2020-2021, when 5% of the population was infected. In conclusion, the effectiveness of the combined NPIs is evident due to the low (<10%) attack rate in the first two waves before vaccines became available, far from the experience of unmitigated COVID-19 in Lombardy in spring 2020, with a 50% attack rate and catastropic levels of severe morbidity and mortality.